2011
DOI: 10.1002/ejic.201100341
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Phosphazene Polymers Containing Photoluminescent Metal Complexes

Abstract: A series of small phosphazene ligands with pendant 6‐phenyl‐2,2′‐bipyridyl moieties, namely L1 [N3P3(OPh)5(OPhbpyPh)], L2 [N3P3(biph)2(OPhbpyPh)2], L3 [N3P3(tBubiph)2(OPhbpyPh)2], L4 [N3P3(biph)2(OPhbpyPh)Cl] and L5 [N3P3(biph)2(OPhbpyPh)(OPh)] [OPhbpyPh = 4‐(4‐phenoxy)‐6‐phenyl‐2,2′‐bipyridine, OPh = phenoxy, biph = 2,2′‐oxybiphenyl and tBubiph = 4,4′‐di‐tert‐butyl‐2,2′‐oxybiphenyl], have been used to synthesise the new cyclometallated palladium(II) and platinum(II) complexes [(L1‐H)PdCl], [(L1‐H)PtCl], [(L1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 65 publications
0
6
0
1
Order By: Relevance
“…The difficulties associated with the process are consistent with reports in the literature . Trifluoroethoxy was not selected as a pendant group because Ainscough et al previously demonstrated that it has a tendency to displace aromatic substituents. Despite the residual P–Cl units, the polymers remained soluble to aqueous workup and remained stable for several months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties associated with the process are consistent with reports in the literature . Trifluoroethoxy was not selected as a pendant group because Ainscough et al previously demonstrated that it has a tendency to displace aromatic substituents. Despite the residual P–Cl units, the polymers remained soluble to aqueous workup and remained stable for several months.…”
Section: Resultsmentioning
confidence: 99%
“…These properties have often proven to be useful in the development of ligands because coordinating substituents (pyridines, phosphines, nitriles, etc.) can be attached to either the cyclotriphosphazene (CTP) to form discrete metal complexes or polyphosphazene (PP) metallopolymers. , Previously reported polymers produced by Ainscough et al proved that the substitution of phosphazenes with fluorophores had little effect on their physical behavior …”
Section: Introductionmentioning
confidence: 99%
“…Among the large class of polyelectrolytes, phosphonium-based polyelectrolytes have attracted increasing interest due to their unique properties such as high thermal stability, flame retardancy, and biocompatibility, leading to potential applications in molecular recognition, , humidity sensors, and biocides . Coexistence of phosphorus centers and metallic centers in macromolecules or the utilization of coordination chemistry in binding the lone pair of electrons on the phosphorus to coordinate metal ions has been known for decades. , The Ragogna Group has utilized photopolymerization methods as a strategy to generate charged, mechanically robust, highly cross-linked phosphonium containing networks with a high degree of surface tunability . By utilizing salt metathesis chemistry of the polyelectrolyte, an anionic gold cluster [(Au 25 L 18 ) − ] was incorporated onto the network ( 2 ; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The ruthenium-bpp-terpy complexes (17 and 18) show little difference in T g relative to that of the parent metal-free polymer for which T g = 36°C. Given the poor agreement with the elemental analysis, a typical issue with post-polymerisation modification [1], other techniques such as electronic absorbance and resonance Raman were employed to determine the formation of the complexes, an approach proven to be effective previously [2,23].…”
Section: Polymer Synthesesmentioning
confidence: 99%